2016
DOI: 10.2217/fon-2016-0253
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding Rnas as Novel Biomarkers in Pancreatic Cancer: what do we Know?

Abstract: Pancreatic cancer is an aggressive cancer of the digestive system, which is becoming a serious health problem worldwide. Overall survival for patients with pancreatic cancer is poor, mainly due to a lack of biomarkers to enable early diagnosis and a lack of prognostic markers that can inform decision-making, facilitating personalized treatment and an optimal clinical outcome. ncRNAs play an important role in pancreatic carcinogenesis. Here we review the literature on the role of ncRNAs as biomarkers in pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 99 publications
0
45
0
Order By: Relevance
“…The authors also showed that ectopic over-expression of miR-181a increases the proliferation of PDAC cells by targeting the ATM gene, while the inhibition of miR-181a in combination with oxaliplatin treatment increased DNA damage and decreased cell viability. The clinical data, together with in vitro findings, strongly suggest the use of miR-181a as a biomarker to select patients responsive to FOLFIRINOX therapy [49,67].…”
Section: Pancreatic Carcinoma (Pdac)mentioning
confidence: 92%
“…The authors also showed that ectopic over-expression of miR-181a increases the proliferation of PDAC cells by targeting the ATM gene, while the inhibition of miR-181a in combination with oxaliplatin treatment increased DNA damage and decreased cell viability. The clinical data, together with in vitro findings, strongly suggest the use of miR-181a as a biomarker to select patients responsive to FOLFIRINOX therapy [49,67].…”
Section: Pancreatic Carcinoma (Pdac)mentioning
confidence: 92%
“…Apart from autoimmune antibodies, other novel markers including serum micro RNAs (miRNAs) signature have been reported to play a role in differentiating pancreatic carcinoma from AIP with high accuracy [26, 27]. MiRNA are endogenous small non-coding RNAs consisting of 19–25 nucleotides, which can interfere with gene transcription and/or translation, thus modulate the targeted gene expression[28].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-16 and miR-196a together with CA19-9, constitute an effective set of first stage tumour markers. Indeed, some workers believe that miRNAs may have a role in assessing a patient's prognosis and their selection for treatment [26]. As an example, upon measuring circulating non-coding RNAs (ncRNAs) in cases of advanced PDAC, useful information can be gained, such as predicting the patient's response to chemotherapy.…”
Section: Nucleotidesmentioning
confidence: 99%